Rheological characterisation of yolk‐based gels and Staphylococcus growth. (30th September 2020) - Alonso, Paula; Laca, Amanda; Laca, Adriana; Díaz, Mario
Summary: Model yolk‐based (10% v/v) gels with different concentrations of κ‐carrageenan (0–2% w/w) were characterised employing rheological measurements, textural analysis and scanning electron microscopy. Additionally, the effect of the microstructure of the model gels on the growth rate of Staphylococcus was also evaluated. In all cases, the nature of the gel was dominated by the elastic component, specifically, 1.5, 1.75 and 2% κ‐carrageenan samples can be described as 'true gels' (tan δ  < 0.1). Maximum strength of the interactions between rheological units ( A ) was observed with 1.75% κ‐carrageenan (4.74 ± 0.38 kPa), which indicates that the strength of interactions was determined not only by κ‐carrageenan concentration, but also by the amount of yolk. Finally, an inverse linear correlation was found between the maximum specific growth rate of Staphylococcus and rheological data ( R 2  > 0.99). Abstract : Overview of the work on rheological characterisation of yolk‐based gels and Staphylococcus growth.